2007
DOI: 10.1007/s00264-007-0355-4
|View full text |Cite
|
Sign up to set email alerts
|

Can radiological results be surrogate markers of functional outcome in distal radial extra-articular fractures?

Abstract: The purpose of this study was to evaluate the relationship between radiological and functional results in patients with extra-articular fractures of the distal radius. We conducted a prospective study of radiological and functional assessment in 95 consecutively selected extraarticular distal radius fractures. There were two patient groups: more than 60 and less than 60 years of age. The final fracture union radiographs were analysed for their functional outcome using the Michigan Hand Outcomes Questionnaire (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 21 publications
(26 reference statements)
4
37
1
4
Order By: Relevance
“…Synn et al [19] cited nine studies that showed no beneficial effect on function despite improved radiological results and 11 studies that had better functional outcomes compared with other treatment methods, but all these studies involved elderly patients. Kumar et al [20] found that the QD after 14 months was related to the radiological results in patients under 60 years of age, but not in patients over 60 years of age. These studies reported medium-term results, between 3 months and 5 years.…”
Section: Locking Plate Fixationmentioning
confidence: 98%
“…Synn et al [19] cited nine studies that showed no beneficial effect on function despite improved radiological results and 11 studies that had better functional outcomes compared with other treatment methods, but all these studies involved elderly patients. Kumar et al [20] found that the QD after 14 months was related to the radiological results in patients under 60 years of age, but not in patients over 60 years of age. These studies reported medium-term results, between 3 months and 5 years.…”
Section: Locking Plate Fixationmentioning
confidence: 98%
“…Their use creates the degree of destructuring caused by loss of the normal palmar angulation of the distal radial, which is difficult to restore and maintain through the methods of closed reduction and immobilization (15) . In this regard, the surgeon's main aim is to achieve an anatomical reduction that is maintained until consolidation, independent of the patient's age (16) .…”
Section: Discussionmentioning
confidence: 99%
“…I seks studier var konklusjonen at radial inklinasjon er av betydning (3, 29-31, 33, 34). I to mente man å kunne påvise en grense ved 15°gjenvaerende radial inklinasjon (29,34), i én en grense ved 10°(31) og i en annen en grense ved 5°(3).…”
Section: Faktorer Av Betydning I Uselekterte Pasientgrupperunclassified
“…I 16 studier fant man at forkorting av radius (økt ulnar varians) var av betydning for resultatet (3,5,(27)(28)(29)(30)(31)(32)(34)(35)(36)(37)(38)(39)(40)(41). Konklusjonen i to studier var at det gikk et skille ved 2 mm ulnar varians (31,41), i to andre gikk skillet ved 3 mm (28, 29) og i én gikk det ved 5 mm (3).…”
Section: Faktorer Av Betydning I Uselekterte Pasientgrupperunclassified
See 1 more Smart Citation